Low-mass members of nearby young stellar moving groups from Gaia EDR3. Issue 4 (10th February 2022) - Lee, Jinhee; Song, Inseok; Murphy, Simon J
ABSTRACT: Gaia EDR3 offers greatly improved kinematics for nearby objects, including members of nearby young stellar moving groups (NYMGs). In this study, we aim to identify low-mass NYMG members (spectral types of M0 to mid-L) in Gaia EDR3. We calculated spatio-kinematic membership probabilities by utilizing a Bayesian membership probability calculation scheme developed in our previous study. We evaluated stellar youth primarily based on colour–magnitude diagram positions. Combining spatio-kinematic membership assessment and youth evaluation, we identified ∼2900 low-mass NYMG candidate members, including ∼700 previously claimed members. In the set of ∼2200 new candidate members, ∼550 appear to be young based on NUV brightness. Our pilot spectroscopic study with Wide Field Spectrograph (WiFeS) on the ANU 2.3-m telescope observed 78 candidates, with 79 per cent confirmed as members. Using our new member sample, we estimated an isochronal age of the β Pictoris Moving Group. The mean age (∼10 Myr), which is around half the age of recent estimates, suggests either a truly younger age of the β Pictoris Moving Group or inaccuracies in contemporary isochrones. As the main results of this study, we provide lists of newly confirmed and candidate low-mass NYMG members.